Serosurvey of selected reproductive pathogens in domestic ruminants from Upper Egypt - Farag, Shimaa Ismail; Cano-Terriza, David; Gonzálvez, Moisés; Salman, Doaa; Aref, Nasr-Eldin M.; Mubaraki, Murad A.; Jiménez-Martín, Débora; García-Bocanegra, Ignacio; Elmahallawy, Ehab Kotb (Frontiers in Veterinary Science, 2023)
Toxoplasmosis, neosporosis, and Q fever are among the most important abortifacient diseases in ruminants worldwide. These diseases result in huge economic losses in livestock besides the fact that some of are of public health concern. The present study aimed to update the data about the current seroepidemiological situation of these diseases in Upper Egypt. A total of 411 blood samples were collected from small and large ruminants and serologically tested against the presence of T. gondii, N. caninum, and C. burnetii. Generalized estimating equation (GEE) models were performed to assess the potential risk factors associated with the exposure to these pathogens. The overall seroprevalence of T. gondii was 47.9% (197/411) with an individual seropositivity of 59.4% (63/106), 58.6% (17/29), 38.8% (54/139) and 46% (63/137) in cattle, buffalo, sheep and goats, respectively. Meanwhile, 9.7% (38/411) of the examined animals were tested positive for anti-N. caninum antibodies, with an individual seropositivity of 13.2 % (12/106), 34.5% (10/29), 8.6% (12/139) and 2.9% (4/137) in cattle, buffalo, sheep and goats, respectively. Furthermore, the overall prevalence of antibodies against C. burnetii was 17.3% (63/411), and exposure to this pathogen was detected in 4.7% (5/106) of cattle, 19.3% (20/129) of sheep, 29.2% (38/130) of goats but none of the examined buffalo were found to be seropositive. A total of 12.1% (50/411) of the examined animals showed co-exposure to at least two of the tested pathogens. Regarding the potential risk factors, there were statistically significant differences among species in the frequency of exposure to the three tested pathogens. Age (> 6 months) was also shown to be a significant risk factor associated with T. gondii exposure. The results obtained provided updated information about the occurrence of three of the main reproductive pathogens in Upper Egypt. The high seropositivity values found for the tested zoonotic pathogens in most of the analyzed ruminant species suggest the necessity of performing additional in-depth studies to evaluate the epidemiology of these pathogens in the study area.